2020
DOI: 10.1002/acr.23907
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Rheumatologist Perspectives Regarding Challenges to Achieving Optimal Disease Control in Rheumatoid Arthritis

Abstract: ObjectiveTo identify and prioritize patient‐ and rheumatologist‐perceived barriers to achieving disease control.MethodsPatients with rheumatoid arthritis (RA) and rheumatologists from the Corrona registry were invited by e‐mail to participate in nominal groups. Two separate lists of barriers were created, 1 from RA patient–only nominal groups and the other from rheumatologist‐only nominal groups, and barriers were sorted into themes. Next, using an online survey, a random sample of RA patients from the Corrona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Another possible interpretation is that patients with a history of cerebrovascular disease are not being treated appropriately. In fact, the physical limitations of patients have been reported to be barriers to achieving optimal disease activity [18], and the usage rate of biologics has been reported to be lower in patients with cerebrovascular disease because this comorbidity is attributed to increased fragility [28]. In this study as well, a high Steinbrocker class was a risk factor for high disease activity in the multivariate logistic regression analysis; impaired physical function was associated with high disease activity.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Another possible interpretation is that patients with a history of cerebrovascular disease are not being treated appropriately. In fact, the physical limitations of patients have been reported to be barriers to achieving optimal disease activity [18], and the usage rate of biologics has been reported to be lower in patients with cerebrovascular disease because this comorbidity is attributed to increased fragility [28]. In this study as well, a high Steinbrocker class was a risk factor for high disease activity in the multivariate logistic regression analysis; impaired physical function was associated with high disease activity.…”
Section: Discussionmentioning
confidence: 47%
“…Using our patient registry with a high proportion of elderly patients, we found that cerebrovascular disease was associated with high disease activity in patients with RA, among the comorbidities studied. Since patients from the registry had a higher average age of 66.4 years, and a higher prevalence of cardiovascular disease (8.0%) and cerebrovascular disease (4.7%) than those in other reports [4,8,18], this finding has important implications for the treatment of rheumatoid arthritis in the elderly.…”
Section: Discussionmentioning
confidence: 80%
“…Financial burden and time have been previously described for patients with RA as a perceived barrier. 25 26 From the qualitative analysis barriers associated with health factors were novel, and not well captured in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…and "What is the difference between joint inflammation and joint damage?" These questions were generated in response to patient-and rheumatologist-identified barriers to T2T in RA (12) and were designed to showcase the benefits of a T2T strategy, as well as address potential patient concerns such as worsening symptoms and the medication side effects some experience when making a medication change. Videos had a mean duration of 2 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Many factors contribute to the observed clinical inertia about RA treatment escalation, including patient–physician therapeutic alliance ( 9 ), topics discussed at the visit, patient satisfaction with the clinical visit ( 10 , 11 ), knowledge about the advantages of following a T2T approach ( 12 ), and variable response to a treatment change ( 13 ). In addition, many patients with RA are concerned about the adverse effects associated with frequently prescribed medications ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%